Evaluation of Static Methods for Predicting Axial Bearing Capacity of Minipiles Using PDA Test Results - Puspa Ningrum; Fadli Azzuhri (Journal of Global Engineering Research and Science, 2026)
Accurate prediction of the axial bearing capacity of pile foundations is essential for ensuring structural safety and optimizing foundation design. Although static prediction methods based on Cone Penetration Test (CPT) data are widely used because of their simplicity and cost-effectiveness, their predictive accuracy varies depending on the adopted analytical approach. This study evaluates the performance of three commonly used static methods (Meyerhof, Schmertmann, and Terzaghi) in predicting the axial bearing capacity of precast concrete minipiles using Pile Driving Analyzer (PDA) test results as the field reference. The analysis was conducted using CPT data collected from six sounding locations at a two-story residential building project in Pekanbaru, Indonesia. The predicted bearing capacities obtained from each method were compared with the ultimate capacity derived from PDA and CAPWAP analyses using absolute and relative differences as evaluation indicators. The results show that all three static methods overestimated the measured pile capacity, although the magnitude of deviation varied considerably. The Schmertmann method produced the highest average predicted capacity (50.35 tons), followed by the Meyerhof method (37.08 tons), while the Terzaghi method yielded the lowest prediction (33.54 tons). Compared with the PDA-derived ultimate capacity of 30.10 tons, the Terzaghi method exhibited the smallest relative difference (11.43%), indicating the closest agreement with field measurements. CAPWAP analysis further revealed that approximately 90.7% of the pile capacity was mobilized through shaft resistance, confirming the predominance of frictional load transfer at the study site. These findings demonstrate that the Terzaghi method provides the most representative prediction of minipile axial bearing capacity under the investigated soil conditions and may serve as a practical alternative for preliminary foundation design when field load testing is unavailable.